Adaptabilitas Padi Gogo di Areal Tanaman Karet Menghasilkan - Sjafei, Gusdi Khamsaldin; Yakup, Yakup; Budianta, Deddik; Sulaiman, Firdaus (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Khamsaldin, S. G., Yakup, Y., Budianta, D., Sulaiman, F, (2023). Adaptability of gogo rice in rubber plant area produces. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 327-332). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Gogo rice is a dryland tolerant crop and can be grown as an intercrop under stands. However, the shade of standing plants is an obstacle to its growth in plantation land, so efforts are needed to obtain gogo rice varieties that are tolerant to shade conditions. This paper aimed to assess the development of hope strains of gogo rice that have multi-tolerant properties to biophysical conditions of drought stress that are resistant to shade through evaluation of the adaptability of selected gogo rice strains. The purpose of this study was to obtain new varieties of shade-resistant gogo rice from 5 shade-treated varieties of gogo rice. 5 varieties of gogo rice. Research was conducted on the growth and production of shade-tolerant gogo rice varieties and NPK doses (50 kg/ha, 75 kg/ha, 100 kg/ha). Genetic information is useful for obtaining new high-yielding varieties of gogo rice. This study begins with seed germination. This research was conducted at the TPH Provincial Agriculture Office. Sumsel. Tools used: polybags, paralon pipes, stationery, This study used a split plot design. This study consists of 2 factors, namely the shade factor (N) as the main plot and the variety factor (V) as the child plot. The watering factor as the main plot consists of 4 levels, namely: N1 = watered every 3 days, N2 = watering every 6 days. While the varietal factor as a plot consists of 5 (five) treatment levels, namely: V1 = Variety 1, V2 = Variety 2, V3 = Variety 3, V4 = Variety 4, and V5 = Variety 5. In total there were 4 main plots and 5 subplots with each treatment repeated 3 times with each trial unit repeated 3 times so that 60 polybags were obtained. Measurements of plant growth variables include: plant height (cm), number of leaves, number of saplings, leaf area (cm2): Calculated using the formula: LD (cm2) = ( p x l x k x n), where p = maximum leaf length, l = maximum leaf width, k = correction factor, n = number of leaves in one plant. Observations of yield variables include: total fresh weight of plants (g) and total dry weight of plants (g), number of productive tillers, panicle length (cm), number of panicle seeds (seeds), weight of seeds per plant, weight of 1000 seeds and % of hollow seeds per plant, proline content. The data collected were analyzed by variety analysis (Test F) at the level of 5%. If there is a noticeable effect (F test 5%) then proceed with the Isolated Real Difference Test (BNT) at the level of 5% to determine the difference between treatments.